Home as a Place for Shaping the Environmental Awareness of Poles - Podkowińska, Monika; Świerczek, Antoni; Balogová, Beáta (Studia Ecologiae et Bioethicae, 2024)
Home is a place where young people grow up, learn and develop the skills necessary for effective participation in society. It is the place where attitudes, opinions, and behaviours of the youngest family members are formed, including those concerning the natural environment. The aim of the article is to explore the role of the family home – specifically the family – in shaping the environmental awareness of Poles. The topic presented in the article is based on the literature on the subject, as well as the results of research on issues related to the environmental awareness of Poles (e.g., CBOS, EcoBarometr, Report on the study of environmental awareness and behaviour of Polish residents 2022). The authors employed desk research to analyse existing data. Studies (EcoBarometr 2023; EcoBarometr 2024) reveal that the primary source of information on the natural environment is the media, rather than the family. For young people, the Internet is becoming the dominant source, while television becomes increasingly significant with age. The results of the research presented in the article also indicate that the vast majority of Poles engage in environmentally friendly activities within their households (e.g. waste segregation). However, the motivations for taking such actions are influenced not only by environmental concerns but also equally by economic considerations. The family environment is not a setting where discussions are a key tool for fostering environmental awareness of Poles. Neither home nor school, in the opinion of the respondents, is the main source of information about the natural environment. This highlights the need to emphasise the family’s role in shaping young people’s environmental attitudes and behaviors.